PENGARUH GAYA KEPEMIMPINAN SITUASIONAL, BEBAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Devianes, Muhammad Fikri; Adi, Agung Nugroho (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the effect of situational leadership style, workload, and work motivation on employee performance at Utama Baja company. This research is explanatory research with a population of 42 people and a sample of 42 people through the total sampling technique. The data analysis tools used are multiple linear regression analysis, instrument test through validizty and reliability test, classical assumption test through normality test, multicollinearity test, linearity test, heteroscedasticity test, and hypothesis testing through t-test, F test, and coefficient of determination test. The results of multiple linear regression analysis show that the variables of situational leadership style, workload, and work motivation effect the employee performance. Then viewed from the Adjusted R Square value, it shows that the magnitude of the influence between variables is 0.671, which means that there is an influence between situational leadership style, workload, and work motivation on employee performance by 67.1 percent while 32.9 percent is explained by other variables not investigated in this study.